Water Quality Status of Way Batanghari River, Metro City, Lampung Province Based on Water Fit for Consumption Parameters - Vifty Octanarlia Narsan; Dimas Ario Setiawan; Astari Rukmana; Rindi Ratna Dewi; Suci Anjarwati; Resi Suhendri (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: The need of water fit for consumption will continue to be sustainable along with the increasing human population, so we need a source of clean water that suitable for consumption. Therefore, this study aims to determine the water quality status of the Way Batanghari river based on an analysis of the feasibility of potable water. Methods: This research used survey method and water sampling in the Way Batanghari tributary, Metro City, Lampung using the consecutive sampling method. Results and Discussion: The physical parameters which include water color exceeds the 50 TCU and indicates the odor of ammonia. The chemical parameters which include COD were 63.5 mg/L (4th class) upstream, 59.3 mg/L (4th class) downstream. DO values upstream were 4.36 mg/L (1st class), 2.83 mg/L (3rd class) downstream. The phosporus value shows a number of 0.54 mg/L (2nd class). pH parameter which shows a value of 7.1 on the upstream, 6.6 on the downstream. Found species from class of Bacillariophyceae, Cyanophyceae as parameters of pollution. Conclusion: Based on Regulation of the Minister of Health, Republic of Indonesia Number 492 of 2010, this river has color and odor of water shows that indicates not meet the requirements for consumption.